Reflecții despre regimul politic din România - Liviu Radu (Revista Transilvană de Ştiinţe Administrative, 2022)
The problem of the leadership structures of human communities is more actual than ever since humanity is facing an ever-increasing number of challenges. Throughout recent history, countries developed three major types of political regimes: presidential, parliamentary, and semi-presidential. All these regimes are subject to criticism and each of them is proving to have advantages and disadvantages. The type of political system of Romania is yet a subject of debate. Although depending on various authors there are different criteria to include a certain political regime among parliamentary or semi-presidential types of the regime, I consider that according to the Constitution, Romania has a pure parliamentary form of government. Though, in practice, Romania seems to resemble what a number of specialists wrote about the French political system. That is, it alternates from a parliamentary to a presidential type of political regime.